Cross-cultural adaptation of the psychological performance inventory-alternative (PPI-A) for the Indonesian context - Miftah Fariz Prima Putra; Sutoro Sutoro; Tri Setyo Guntoro; Evi Sinaga; Tery Wanena; Kurniati Rahayuni; Miftakhul Jannah; Weni Endahing Warni; Juriana Juriana; Anung Priambodo; Kurnia Tahki; Imam Hariadi; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
In Indonesia, studies on the theme of sports psychology, especially mental toughness, are experiencing an increasing trend. However, there are problems with the measuring instruments used. Therefore, this research aims to adapt and test the psychometric properties of the PPI-A in the Indonesian context. There were 331 young athletes (M = 218, F = 113) with a mean age of 17.9 years and a standard deviation of 2.09. Apart from the psychological performance inventory-alternative (PPI-A), the mental toughness index (MTI) was also used to collect data in this study. The data obtained were analyzed using confirmatory factor analysis (CFA) to test the three models (single-factor model, four-factor model, and second-order model) proposed. The research results show that the second-order model is the best compared to the unidimensional model and four-factor model, as evidenced by the chi-square value = 47.934; df = 32; p = .002; CFI = .961; GFI = .969; TLI = .938; SRMR = .038; RMSEA = .057. Of the fourteen items in the PPI-A, nine items had very good loading factor (λ = .563 to .759; p < 0.001). The internal consistency reliability of the PPI-Aid is moderate (α = .74 to .77) while the reliability with convergent validity is in the small to moderate category (r = .16 to .35; p ≤ .01). Even though the reliability value is not high, it can be stated that PPI-Aid is a valid and reliable measuring tool in measuring aspects of mental toughness.